Navigating EFL Teachers' Challenges with Digital Technologies in Project-Based Learning in the English Classroom - Diah Khoirunnisa Harahap; Sholihatul Hamidah Daulay; Utami Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to explore the challenges experienced by EFL teachers in utilizing digital technologies in implementing Project–Based Learning in English classrooms. This study employed a qualitative descriptive research design to explore the challenges faced by EFL teachers in utilizing digital technologies within the implementation of Project-Based Learning (PjBL) in English classrooms. The participants consisted of two EFL teachers from North Sumatera, Indonesia, who have implemented PjBL and integrated digital technologies in their English language teaching. A purposive sampling technique was employed to select teachers who currently teaching English at junior high school level. The findings show that teachers encounter four main types of challenges: technical issues such as poor internet and limited devices; pedagogical difficulties including limited training and confidence in designing digital PjBL; institutional barriers like unclear policies, lack of technical support, and limited budgets; and student-related problems such as uneven digital skills and low motivation.